Predictive value of plasma asymmetric dimethylarginine, homocysteine, and high-sensitive CRP levels in occult coronary artery disease A multidetector-row computed tomography study - TİGEN, MUSTAFA KÜRŞAT (URBAN & VOGEL, 2015)
Background. Multidetector-row computed tomography (MDCT) is an attractive noninvasive imaging modality for detecting coronary atherosclerotic plaques, which may be underestimated by conventional angiography. The aim of our study was to determine the predictive value of plasma asymmetric dimethylarginine (ADMA), homocysteine, and high-sensitivity C-reactive protein (hsCRP) levels for occult coronary artery disease (CAD). Patients and methods. Thirty-five patients with angiographically normal coronary arteries (NCA) were consecutively included in our study. They underwent MDCT including indications and were divided into an NCA group (18 subjects, 8 male, 46 +/- 8 years) and an occult CAD group (17 subjects, 11 male, 48 +/- 9 years), with respect to the presence of coronary plaque. Plasma ADMA, homocysteine, and hsCRP levels were measured in blood samples. Results. Plasma ADMA and homocysteine levels of the occult CAD group were significantly higher than those of the NCA group. A nonsignificant trend was observed for higher serum hsCRP levels in the occult CAD group. Receiver operating characteristics analysis revealed that an ADMA level of >0.71 mu mol/l could predict patients with occult CAD (sensitivity, 76%; specificity, 67%). The discriminative power of ADMA in distinguishing the occult CAD group from the NCA group was high area under the curve, 0.80; CI, 0.66-0.95, p=0.002), while it was not sufficiently high for homocysteine and hsCRP (p>0.05). Conclusion. Plasma ADMA is a useful parameter for predicting subclinical atherosclerosis, whereas homocysteine and hsCRP are not, and it may be complementary to the conventional cardiovascular risk factors for the selection of individuals at high risk for CAD before undertaking MDCT procedures in clinical practice.
Keywords: Coronary artery disease; Computed tomography; Atherosclerosis; Asymmetric dimethylarginine; Risk factors; C-REACTIVE PROTEIN; FACTOR INTERVENTION TRIAL; HEART-DISEASE; CARDIOVASCULAR-DISEASE; RISK-FACTOR; INTRAVASCULAR ULTRASOUND; ATHEROSCLEROTIC PLAQUE; ANGIOGRAPHY; METAANALYSIS; MORTALITY